Great recession, slow recovery and muted fiscal policies in the US - Alice Albonico; Patrizio Tirelli; Alessia Paccagnini (University College Dublin, UCD School of Economics, 2016)
This paper reconsiders the role of macroeconomic shocks and policies in determining the Great Recession and the subsequent recovery in the US. The Great Recession was mainly caused by a large demand shock and by the ZLB on the interest rate policy. In contrast with previous findings, the subsequent jobless recovery is explained by the ZLB effect. We estimate a fraction of non-Ricardian households which is close to 50%, and obtain comparatively large fiscal multipliers. However we cannot detect a signi.cant contribution of fiscal policies in stabilizing the US economy. For instance, the 2007-2009 large increase in expenditure-to- GDP ratios was apparently determined by the adverse non-policy shocks that caused the recession.
Keywords: C11; C13; C32; E21; E32; E37; 330; DSGE; Limited Asset Market Participation; Bayesian Estimation; US Economy; Business Cycle; Monetary Policy; Fiscal Policy